The development of national multisectoral action plans for the prevention and control of noncommunicable diseases: experiences of national-level stakeholders in four countries. Issue 1 (1st January 2018) - Wickramasinghe, Kremlin; Wilkins, Elizabeth; Foster, Charlie; Fadhil, Ibtihal; Hammerich, Asmus; Slama, Slim; El Berri, Hicham; Elimam, Manal; Adib, Salim; Al-Mudwahi, Mona; Townsend, Nick
ABSTRACT: Background : In October 2012, the WHO Eastern Mediterranean Region (EMR) developed a Regional Framework for Action to implement multisectoral action plans (MAPs) for the prevention and control of noncommunicable diseases (NCDs). Objectives : The aim of this project was to draw on the experiences of four EMR countries that had made good progress in developing these MAPs, to identify best practice and barriers in the development of them. Methods : Structured interviews were held with key stakeholders in the development of the MAPs from the four focal EMR countries: Lebanon, Morocco, Sudan, and Yemen. These interviews comprised two stages: first we conducted face-to-face interviews in September 2014; we then carried out follow-up teleconference interviews during October 2014. Thematic analysis of transcripts was used to identify several themes, including examples of best practices and challenges that were common to all four focal countries and are likely to be also relevant to many other countries in the development of MAPs. Results : Best practice in the development of MAPs includes methods to identify and recruit key sectors, ways to foster collaboration between sectors in the development and implementation of the action plan and means through which to encourage public support. Challenges identified included measuring outcomes in evaluating MAP success, current pressures and competing priorities for sectors and the perception of health issues as the responsibility of the health sector. Cultural and bureaucratic challenges were also discussed along with multisectoral fatigue, through the promotion of multisectoral approaches for a number of national issues. Conclusions : Although the development of multisectoral action plans to tackle NCDs is recommended, the process is a challenging one. Reflections from those countries which have experience in developing such action plans is important in identifying common challenges as well as recommending best practice, such that other countries may learn from their experiences.